Pedagogical Ways Of Forming Linguistic Capacities In The Teaching Process Of Methodology Of Preschooler's Speech Development Training Course - Amiraghyan, M. G. (Մանկավարժ հրատ․)
The article discusses the need to review "Methodology of preschooler’s speech development" teaching course for senior preschoolers due to senior preschoolers' speech difficulties identified during the experiment and with insufficient theoretical and practical approaches to the problem. As a solution to the issue, pedagogical ways of forming linguistic capacities by ensuring senior preschooler's self-manifestation and free self-expression are proposed, which will enrich the content of the above-mentioned training course, at the same time contributing to the professional advancement of future specialists. Հոդվածում քննարկված է «Նախադպրոցականի խոսքի զարգացման մեթոդիկա» դասընթացի վերանայման անհրաժեշտությունը՝ պայմանավորված ավագ նախադպրոցականների խոսքային դժվարությունների բացահայտման հանգամանքով և խնդրի վերաբերյալ ոչ բավարար տեսագործնական մոտեցումներով։ Առաջարկվում են ավագ նախադպրոցականների ինքնադրսևորման ու ազատ ինքնարտահայտման ապահովմամբ լեզվական կարողությունների ձևավորման մանկավարժական ուղիներ, որոնք հարստացնում են դասընթացի բովանդակությունը՝ նպաստելով ուսանողների մասնագիտական առաջընթացին։ В статье обсуждается необходимость пересмотра учебного курса «Методика развития речи дошкольников» для старших дошкольников в связи с выявленными в ходе эксперимента речевыми трудностями и недостаточным теоретическим и практическим подходами к проблеме. В качестве решения проблемы предлагаются педагогические пути формирования языковых способностей за счет обеспечения свободного самовыражения старшего дошкольника, которые обогатят содержание вышеуказанного учебного курса, одновременно способствуя профессиональному росту будущих специалистов.
Keywords: Pedagogy; Speech Development